Emodin Protects Against Lipopolysaccharide-Induced Acute Lung Injury via the JNK/Nur77/c-Jun Signaling Pathway - Xie, Pei; Yan, Li-Jun; Zhou, Hong-Ling; Cao, Hui-Hui; Zheng, Yuan-Ru; Lu, Zi-Bin; Yang, Hua-Yi; Ma, Jia-Mei; Chen, Yu-Yao; Huo, Chuying; Tian, Chunyang; Liu, Jun-Shan; et al. (Frontiers in Pharmacology, 2022)
Background: In modern warfare, combat injury is a critical cause to develop into acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) without effective treatments. Although emodin from Rheum palmatum L. exerts anti-ALI properties, the underlying mechanisms have not been fully explored. Purpose: This study aimed to investigate the therapeutic effect and mechanism of emodin on LPS-induced ALI in mice. Methods: RAW264.7 cells and zebrafish larvae were stimulated by LPS to established inflammatory models. The anti-inflammatory effect of emodin was assessed by ELISA and survival analysis, respectively. In vitro mechanisms were explored by using Western blotting, luciferase assay, electrophoretic mobility shift assay (EMSA) and small interfering RNA (siRNA) approach and overexpression assay. The acute lung injury model in mice was established by intratracheal administration of LPS and the underlying mechanisms were assessed by detecting changes in hispathological and inflammatory markers and Western blotting in lung tissues. Results: Emodin inhibited the secreation of TNF-α and IL-6 in RAW264.7 cells and prolonged the survival of zebrafish larvae after LPS stimulation. Emodin suppressed the expression levels of JNK at Thr183/tyr182, c-Jun at Ser73 and Nur77 at Ser351 and increased the expression level of Nur77 in LPS-stimulated RAW264.7 cells. while these effects of emodin were counteracted by JNK activator. Overexpression of JNK dampened emodin-mediated increase in Nur77 luciferase activity. Moreover, the inhibitory effect of emodin on c-Jun can be attenuated by Nur77 siRNA. Furthermore, emodin alleviated LPS-induced ALI in mice through regulation of the JNK/Nur77/c-Jun pathway. Conclusions: Emodin protects against LPS-induced ALI through regulation on JNK/Nur77/c-Jun signaling. Our results indicate the potential of Emodin in the treatment of ALI.